ANALISIS KESESUAIAN RUANG TERBUKA HIJAU DALAM POLA RUANG RENCANA DETAIL TATA RUANG (RDTR) : STUDI KASUS KOTA JAKARTA SELATAN - Athif Washfa Syadi Syah; Sony Nugratama Hijrawadi; Muhammad Yusuf (Universitas Nusa Cendana, 2026)
This study aims to analyze the conformity of Green Open Space (RTH) distribution in South Jakarta in 2014 and 2024 with the spatial pattern defined in the Detailed Spatial Plan (RDTR). This research uses a quantitative approach with spatial analysis based on Geographic Information Systems (GIS) and remote sensing. The main data include Landsat 8 imagery and RDTR documents. Land cover classification was conducted using the Maximum Likelihood Classification (MLC) method, followed by overlay analysis to determine conformity levels. The results show that RTH in South Jakarta is still dominated by conforming areas, but there is a decline over time. The conforming RTH area decreased from 932.15 hectares (6.59%) in 2014 to 892.23 hectares (6.31%) in 2024. Meanwhile, non-conforming RTH increased from 40.16 hectares to 80.08 hectares. The largest decrease occurred in Jagakarsa (13.02 ha), followed by Pesanggrahan (5.41 ha) and Cilandak (5.04 ha). Compared to Law No. 26 of 2007 requiring 30% green open space, the RTH proportion in South Jakarta is still far below the standard.